Adsorption of colour from dye wastewater effluent of a down-flow hanging sponge reactor on purified coconut fibre. Issue 10 (28th April 2020) - Nguyet, Phan Nhu; Hata, Yuya; Maharjan, Namita; Watari, Takahiro; Hatamoto, Masashi; Yamaguchi, Takashi
ABSTRACT: This study was carried out to evaluate the potential application of agricultural waste coconut ( Cocos nucifera ) fibre in its purified form for decolorization of dye-containing effluent from a down-flow hanging sponge (DHS) reactor. Batch adsorption experiments were conducted by varying adsorbent dose, solution pH, contact time and temperature. The results showed that the adsorption percentage of colour increased with increasing in adsorbent dosage from 0.1 g to 1.3 g, solution pH from 2 to 10 and contact time from 1 h to 72 h. The adsorption process was sensitive to temperature and the adsorption percentage of colour reached the highest value at 30°C but decreased when temperature increased from 30°C to 60°C. Purified coconut fibre (PCF) had a good adsorption capacity under the optimal conditions of an adsorbent dose of 0.7 g, pH 8, temperature of 30°C and 24 h contact time. The equilibrium data were well fitted to both Langmuir and Freundlich isotherms, and the best fit of equilibrium isotherms was described using the Freundlich isotherm model. The Langmuir maximum adsorption capability of the PCF was found to be 303 (Pt/Co)/g at 30°C. The results of this study indicated the applicability of PCF as post-treatment unit of DHS reactor for removal of colour in the industrial dye effluent. GRAPHICAL ABSTRACT: